Efficient diels-alder reaction of 1,2-benzoquinones with arynes and its utility in one-pot reactions - Kaicharla, Trinadh; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
A new protocol for the efficient Diels–Alder reaction of 1,2-benzoquinones with arynes is reported. The aryne generated by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes a facile Diels–Alder reaction with 1,2-benzoquinones, affording the dioxobenzobicyclooctadienes in moderate to excellent yields. In addition, this methodology has been applied to the one-pot synthesis of benzoquinoxalinobarrelene and naphthalene derivatives.

Employing arynes in transition-metal-free monoarylation of aromatic tertiary amines - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Biju, Akkattu T. (Organic Letters, 2013)
The highly monoselective N-arylation of aromatic tertiary amines using a transition-metal-free approach using arynes has been developed. The reaction afforded functionalized diaryl amines in moderate to excellent yield. High levels of functional group compatibility especially with halogen containing substrates, dyes and donor-acceptor systems, and high yields of products are the notable features of the present reaction.

Engaging isatins in solvent-free, sterically congested passerini reaction - Kaicharla, Trinadh; Yetra, Santhivardhana Reddy; Roy, Tony; Biju, Akkattu T. (Green Chemistry, 2013)
A facile, atom-economic and environmentally-benign protocol for the synthesis of biologically important oxindole derivatives in high yields has been demonstrated by employing isatins as carbonyl compound surrogates in a Passerini reaction carried out under solvent-free conditions. Moreover, electron-deficient phenols can also be used as the acid component in this reaction. In addition, the synthetic utility of the present methodology was examined by the one-pot synthesis of oxindoles with a free -OH group at the benzylic position.

Employing carboxylic acids in aryne multicomponent coupling triggered by aziridines/azetidines - Roy, Tony; Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Thangaraj, Manikandan; Garai, Bikash; Biju, Akkattu T. (Organic Chemistry Frontiers, 2016)
The transition-metal-free aryne multicomponent coupling (MCC) involving carboxylic acids initiated by aziridines/azetidines has been reported. The use of aziridines as nucleophiles afforded N-aryl beta-amino alcohol derivatives and the application of azetidines as nucleophilic triggers furnished N-aryl gamma-amino alcohol derivatives in moderate to good yields. These reactions proceed under mild conditions and result in the formation of a new carbon-nitrogen bond and a new carbon-oxygen bond. The utility of carboxylic acids in aryne MCCs has been demonstrated, and the synthetic potential of phenols as acid surrogates in the present aryne MCCs has been realized.